2021
DOI: 10.1002/jtr.2482
|View full text |Cite
|
Sign up to set email alerts
|

When souvenirs meet online shopping – the effect of food souvenir types on online sales

Abstract: This study classified food souvenirs into four categories based on two dimensions of product characteristics (i.e., brand awareness and local relevance) and investigated the differences in their online sales. We also explored the role of online sales platforms and geographical distance in moderating the sales differences among different categories of food souvenirs. Real sales data were collected from a regional enterprise that sells food souvenirs on both local and national online shopping platforms.The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 82 publications
(161 reference statements)
0
19
0
1
Order By: Relevance
“…Agar respon yang diberikan akurat, wisatawan diminta untuk merespon kuesioner setelah mereka berbelanja produk kuliner khas Bandung. Persepsi turis terhadap desain visual kemasan produk kuliner khas Bandung dalam berbelanja suvenir sebagai makanan akan dianalisa dengan menggunakan deskriptif statistik, sedangkan hubungan antara persepsi positif terhadap desain visual kemasan dengan kualitas produk kuliner khas Bandung akan dianalisis menggunakan analisa regresi (Yuan, Xie, Li, & Shen, 2022).…”
Section: Metodeunclassified
“…Agar respon yang diberikan akurat, wisatawan diminta untuk merespon kuesioner setelah mereka berbelanja produk kuliner khas Bandung. Persepsi turis terhadap desain visual kemasan produk kuliner khas Bandung dalam berbelanja suvenir sebagai makanan akan dianalisa dengan menggunakan deskriptif statistik, sedangkan hubungan antara persepsi positif terhadap desain visual kemasan dengan kualitas produk kuliner khas Bandung akan dianalisis menggunakan analisa regresi (Yuan, Xie, Li, & Shen, 2022).…”
Section: Metodeunclassified
“…Previous research proposed four categories of food souvenirs, namely traditional culture, new commercial culture, local food, and ordinary food (Yuan et al, 2022). Food souvenirs are purchased to be eaten outside the place of purchase (Yuan et al, 2022). The same study found that the online marketing of new culture commercial food souvenirs was higher than that of local food souvenirs.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers pay attention to the strength of product locality, especially in the national online market. However, the customer's willingness to choose food with a strong local character (traditional culture and local food souvenirs) can be reduced in the national online market (Abendroth, 2011;Yuan et al, 2022). This finding indicated the potential for a new culture of commercial or popular food in the local online food souvenir market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations